A novel fluorescence and resonance Rayleigh scattering probe based on quantum dots for the detection of albendazole. Issue 2 (1st December 2014) - Li, Qin; Tan, Xuanping; Fu, Lingli; Liu, Qu; Tang, Weiwei
Abstract : Glutathione (GSH)-capped CdTe QDs with diameters of 3 nm were synthesised. Abstract : Glutathione (GSH)-capped CdTe QDs with diameters of 3 nm were synthesised. The interaction between the QDs and albendazole (ABZ) was investigated by UV-vis absorption, resonance Rayleigh scattering (RRS) and fluorescence spectroscopy. Based on changes in the UV-vis absorption spectra of QDs and ABZ, we demonstrated that the QDs associated with ABZ to form new complexes. In pH 7.1 PBS buffer solution, the fluorescence intensity of QDs was effectively quenched by ABZ. The fluorescence quenching of QDs by ABZ mainly results from the QDs–ABZ complexes, and the electrostatic attraction played a major role in stabilising these complexes. Furthermore, the interaction between QDs and ABZ led to a remarkable enhancement in RRS, which was proportional to the ABZ concentration within a certain concentration range. The suitable reaction conditions, important factors as well as the influence of coexisting substances were studied. The possible reaction mechanism was also discussed.